Tuberculosis of Sphenoid Sinus: Report of Two Cases - Bhat, Vadisha Srinivas; J., Samatha K.; T., Devika; P., Shrinath D. Kamath; Aroor, Rajeshwary; B., Satheesh Kumar Bhandary (Journal of Health and Allied Sciences NU, 2020)
Isolated lesions of the sphenoid sinus are uncommon and difficult to diagnose. In the absence of characteristic clinical findings, the diagnosis of such lesions depends mainly on imaging. However, as radiological appearance cannot provide the clinician with a definite diagnosis, histopathological examination of the specimen is mandatory for the diagnosis. Endoscopic sinus surgery has been an excellent approach for diagnosis as well as treatment of isolated sphenoid sinus lesions. The disease can be effectively treated by antituberculosis treatment. We report two cases of tuberculosis involving the sphenoid sinus only.
Keywords: tuberculosis; sphenoid sinus; endoscopic sinus surgery; antituberculosis treatment